Molecular Science of Fluctuations Toward Biological Functions - Terazima, Mazahide; Kataoka, Mikio; Ueoka, Ryuichi; Okamoto, Yuko.; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2016)
In this monograph, the importance of fluctuations for biological reactions is discussed from various points of view. Understanding the biological reactions at the molecular level is one of the major targets in many scientific fields, including not only basic biology but also physics, physical chemistry, and medical science. One of the key factors in the process is "fluctuation". Thermal energy causes biological molecules to be in constant fluctuation even while they are carrying out their biological functions. How do biological systems overcome the thermal fluctuations to realize the physiologically relevant reactions? Scientists in a number of fields-physics, chemistry, pharmacology, medicine, and others-have contributed chapters that elucidate the nature of the fluctuations and the relationship between fluctuations and biological functions. The fluctuations discussed in this volume are detected by the transient grating method, nuclear magnetic resonance, X-ray diffraction and scattering, and computer simulation, among other methods. The book presents various results of the studies of fluctuations in biological processes that were obtained with these methods by the leading scientists in their fields. .
Time-resolved detection of protein fluctuations during reactions -- Pressure perturbation: A prime tool to study conformational substates and volume fluctuations of biomolecular assemblies -- Watching a signaling protein function in real time via picosecond time-resolved Laue crystallography -- NMR explorations of biomolecular systems with rapid conformational exchanges -- Site-specific incorporation of fluorescent nonnatural amino acids in-to proteins and its application to fluorescence analysis of proteins -- Unfoldomes and unfoldomics: introducing intrinsically disordered proteins -- Structure, dynamics and function of staphylococcal nuclease -- Theory of molecular recognition and structural fluctuation of biomolecules -- Structural fluctuations of proteins in folding and ligand docking studied by replica-exchange simulations -- Spatio-temporal fluctuations of protein folding in living cells -- Membrane-targeted nanotherapy with hybrid liposomes for cancer cells leading to apoptosis -- Anti-tumor complexes formed by oleic acid and molten globule intermediates of proteins.
Keywords: Bioorganic chemistry; Proteins .; Biophysics; Physical chemistry; Bioinformatics; Medicine -- Research; Biology -- Research; Bioorganic Chemistry; Protein Biochemistry; Biophysics; Physical Chemistry; Computational and Systems Biology; Biomedical Research